De la jeunesse sexuelle à la sexualité conjugale, des femmes en retrait - Emmanuelle Santelli (Genre, Sexualité et Société)
Starting with an empirical survey conducted in 2016 on about 40 young adults in “stable couples,” this article aims to understand how, within a few years, a majority of women who were sexually active in their youth tend to lose interest for heterosexual conjugal sexuality. Even though young women have been able to have more sexual and sentimental experiences than ever before in history, we note that once couples are formed, expectations towards sexuality diverge. This is often attributed to male “needs,” which are perceived as harder to control. Our article will show how women negotiate these needs, and how, in this context, sexual activity is used to maintain the conjugal bond. Only a few younger women, among those surveyed, declare that they still experience sexual attraction. This heterogeneity leads us to further investigate why sexual activity becomes of less interest to women and to offer a hypothesis in terms of a lesser socialization of the desiring component of sexuality.